Silane Heat Treatment Could Eliminate the Hydrofluoric Acid Etching of Lithium Disilicate Overlays: A Four-Year Follow-Up - Spartak Spasov Yanakiev; Mirela Borislavova Marinova-Takorova (Case Reports in Dentistry)
A four-year follow-up of a novel silane heat treatment method for bonding lithium disilicate overlays to tooth structures without hydrofluoric acid etching of the ceramic surface is presented in this case report. Silane heat treatment modifies the silane layer and thus enhances resin ceramic bond strength without hydrofluoric acid etching. The standard ceramic preparation technique prior to bonding silicate ceramics to tooth structure is hydrofluoric acid etching and applying a silane coupling agent, followed by dental adhesive. In this case, the micromechanical roughening of the ceramic surface was performed by air abrasion with Al2O3. Silane heat treatment with constant 120°C airflow, applied for 60 sec, followed by dental adhesive application enhanced the resin-ceramic bond strength. After a four-year follow-up, the restorations’ clinical appearance could be defined as excellent/very good according to the FDI clinical criteria for the evaluation of direct and indirect restorations. This clinical result supports many in vitro studies regarding the resin-ceramic bond strength and durability obtained through postsilanization heat treatment.